Agroforestry Extension and its Impact on Socio-economic Scenario - a Case Study of Yamunanagar District (Haryana) - Kumar, Rajiv; Gupta, P. K.; Gulati, Ajay (Indian Forester, 2003)
Agroforestry in India has been identified as a potential practice, which can contribute significantly in increasing tree cover; meeting people's requirement of fuel wood, fodder, timber and non timber forest products. It can also ensure supply of raw material to the forest based industries and creating large scale employment opportunities. The present article discusses as to how a well-planned and systematic approach in agroforestry extension can attract farmers to adopt agroforestry practices and initiate a diffusion process, under which the practice spreads by itself due to its inherent virtues. About nine years back agroforestry was in its infancy stage, when the systematic and intensive extension works were initiated in Yamunanagar District of Haryana State. Today, on an average 30% of the total income of a family comes from agroforestry. This additional income has brought radical changes in the social life of rural people. They enjoy better education and have access to basic and modern amenities. Farmers with big land holdings have been benefited most by the agroforestry extension work. There is a need to chalk out special programme for development of agroforestry on the lands of small and marginal farmers.